Evaluating Stiffness of Fibreglass and Thermoplastic Splint Materials and Inter-fragmentary Motion in a Canine Tibial Fracture Model - Wagoner, Amanda L.; Allen, Matthew J.; Zindl, Claudia; Litsky, Alan; Orsher, Robert; Ben-Amotz, Ron (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objectives Various materials are used to construct splints for mid-diaphyseal tibial fracture stabilization. The objective of this study was to compare construct stiffness and inter-fragmentary bone motion when fibreglass (FG) or thermoplastic (TP) splints are applied to either the lateral or cranial aspect of the tibia in a mid-diaphyseal fracture model.Methods A coaptation bandage was applied to eight cadaveric canine pelvic limbs, with a custom-formed splint made of either FG or TP material applied to either the lateral or cranial aspect of the osteotomized tibia. Four-point bending tests were performed to evaluate construct stiffness and inter-fragmentary motion in both frontal and sagittal planes.Results For a given material, FG or TP, construct stiffness was not affected by splint location. Construct stiffness was significantly greater with cranial FG splints than with cranial TP splints (p < 0.05), but this difference was not significant when comparing splints applied laterally (p = 0.15). Inter-fragmentary motions in the sagittal and frontal planes were similar across splint types for cranial splints, but for lateral splints there was a 64% reduction in frontal plane motion when FG was used as the splint material (p = 0.03).Clinical Significance FG produces a stiffer construct, but the difference is not reflected in a reduction in inter-fragmentary motion. For lateral splints, FG splints are associated with reduced inter-fragmentary motion as compared with TP and may therefore have slight superiority for this application.
Keywords: biomechanics; fracture stabilization; long bone fractures; mechanical testing; motion analysis